2021
DOI: 10.1007/s11739-021-02784-y
|View full text |Cite
|
Sign up to set email alerts
|

Patients with hematologic cancers are more vulnerable to COVID-19 compared to patients with solid cancers

Abstract: Previous studies reported that COVID-19 patients with cancer had higher rates of severe events such as intensive care unit (ICU) admission, mechanical ventilation (MV) assistance, and death during the COVID-19 course compared to the general population. However, no randomized study compared the clinical course of COVID-19 in patients with hematologic cancers to patients with solid cancers. Thus, in this study, we intend to reveal the outcome of COVID-19 in hematologic cancer patients and compare their outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…In our patients with CML, the prevalence of Covid‐19 infections did not differ significantly from the general Austrian population as well. Such a low prevalence of Covid‐19 infections among patients with CML was also reported in several other papers 38,39,43,44 . Of note, most of these CML patients were in chronic phase and/or had a stable course in response to TKIs 43,47,48 .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In our patients with CML, the prevalence of Covid‐19 infections did not differ significantly from the general Austrian population as well. Such a low prevalence of Covid‐19 infections among patients with CML was also reported in several other papers 38,39,43,44 . Of note, most of these CML patients were in chronic phase and/or had a stable course in response to TKIs 43,47,48 .…”
Section: Discussionsupporting
confidence: 61%
“…Published data report a higher risk for Covid‐19 infections in patients with certain hematologic neoplasms as compared to the general population or patients with solid tumors 36–41 . Such diseases were acute leukemia, advanced MDSs, or lymphomas 22,27,39–41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 1871 identified references, a total of 67 studies accounting for 10,061 hematological patients and 111,143 controls were included in the systematic review (Table S3 summarizes the included studies and reported outcomes). 13 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , ...…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Previous research revealed that patients with hematologic cancers (HC) experienced more severe COVID-19 symptoms and higher CFR (case fatality rate) side to those with solid cancers (SC). 6 More severe manifestation and higher CFR are found in hematologic cancer patients compared to solid cancer patients.…”
Section: Introductionmentioning
confidence: 99%